The process theories of motivation in cross-cultural context - Тургумбаева, Айжан; Аймагамбетова, Ольга Хабижановна (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2017)
The articles discusses the process theories of motivation represented by expectancy theory of V.Vroom, model of Porter-Lawler, theory of justice of G. Adams and goal-setting theory of E. Locke and its new role in the cross-cultural context. The process theories basically focused on “how” performance let the reveal the existence or absence of differences among representatives of different cultural and ethnical groups in terms of motivational factors. In the era of clashing civilizations and cultures, it is important to identify the motivational drivers for sustainable and successful development of any organization including the academia. The crosscultural context is extremely important in the last few years with the rise of transnational companies and internationalization of higher education. In this sense, the study of motivational drivers of representatives of different cultures can lay the foundation for further research of motivation in crosscultural context. The overview reveals the necessity to look at the existing theories from the new edge, considering the cultural differences and peculiarities, as well as the new challenges of globalizing world. Key words: motivation, process theory, cross-cultural context, cultural differences, national context.